Technical Guidance for Making Teaching Modules for Primary School Teachers in the Toho District - Hery Kresnadi; Dyoty Auliya Vilda Ghasya; Siti Halidjah; Kartono; Asmayani Salimi; Rio Pranata; Agung Hartoyo; Neni Mariyani (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Education is an important factor in the development of the country, and the quality of education needs to be improved. One of the efforts to improve the quality of education is the development of teaching modules that are by the Merdeka Curriculum. However, the implementation of the Merdeka Curriculum in elementary schools in The Toho District is still experiencing obstacles. The lack of teachers' understanding and skills in making teaching modules is the main factor that hinders them. Therefore, this study conducted technical guidance on making teaching modules for the Merdeka Curriculum for elementary school teachers in Toho District. In this technical guidance, a Direct Instruction approach is used with four stages: socialization, discussion, practice making teaching modules in groups, and evaluation. The results show an increase in teachers' understanding of the Merdeka Curriculum, their confidence in implementing teaching modules, and the development of high-quality teaching modules. Despite the success, the evaluation identified some challenges, including the perception that some learning objectives should be taught in a single meeting.